PERAN PENYULUH PERTANIAN TERHADAP PENINGKATAN PRODUKSI PADI SAWAH DI DESA LUBUK SINI KECAMATAN TABA PENANJUNG KABUPATEN BENGKULU TENGAH - Fitria, Indah (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2025)
Taba Penanjung Subdistrict, Central Bengkulu Regency, is one of the areas with an underdeveloped standard of living where most of the population still relies on farming, particularly as rice paddy farmers. In this study, 26 rice paddy farmers were surveyed. Technique sampling was determined using a simple random sampling method, which allows each member of the population an equal chance of being selected as a sample. Additionally, four agricultural extension workers were added as correspondents.  Agricultural extension workers play a very important role, as can be seen from the recap of the average scores of agricultural extension activities: X1 (extension workers as guides) with an average score of 3.72 and a total of 96.5, X2 (extension workers as organizers and dynamizers) with an average score of 3.23 and a total of 83.75, then X3 (extension workers as technicians) with an average score of 3.08 and a total of 80, and X4 (extension workers as consultants) with an average score of 3.06 and a total of 79.3. This shows that X1 demonstrates very good results compared to X2, X3, and X4, and the presence of agricultural extension workers has a positive impact on the economic welfare of farmers in Lubuk Sini Village. This is evidenced by rice production results with an average of 7.290 kg/mt. In the improvement of farming enterprises, it is hoped that the sustainability of extension services in agriculture and technology will continue, whether by the government or private sectors, to enhance the achievements of these farmers.